The international normalized ratio calibrated for cirrhosis (INRliver) normalizes prothrombin time results for model for end‐stage liver disease calculation - Tripodi, Armando; Chantarangkul, Veena; Primignani, Massimo; Fabris, Federica; Dell'Era, Alessandra; Sei, Cinzia; Mannuccio Mannucci, Pier (Hepatology (Baltimore, Md.), 2007)
The model for end‐stage‐liver‐disease (MELD) is a mathematical score used to prioritize patients for liver transplantation and includes results for creatinine, bilirubin, and prothrombin time (PT) expressed as international normalized ratio (INR). The rationale of using the MELD rests on the assumption that the score would be the same across the country if the methods used to measure the variables yield the same numerical results regardless of the testing laboratory. Evidence was provided that specific methodologies may influence the MELD, and the PT‐INR was identified as the most important. This study was designed to provide information on the between‐thromboplastin variability and to explore alternatives to obviate such variability. Fifty‐seven patients with cirrhosis were selected, and their PTs were measured with 7 thromboplastins. The thromboplastins were previously calibrated by testing plasmas from patients on vitamin K antagonists and healthy subjects to assign the international sensitivity index (ISIvka) needed to convert PT into INR. Each of the thromboplastins was also assigned an ISIliver by substituting in the calibration the plasmas from vitamin K antagonist patients with plasmas from patients with cirrhosis. INR and MELD values for individual patients were calculated by using the ISIvka or the ISIliver. The mean INRvka obtained with the 7 thromboplastins were significantly different (P < 0.001). Conversely, the mean INRliver were not. Similarly, the mean MELDvka were significantly different (P < 0.001), but those differences were abrogated for the MELDliver. Conclusion: The alternative thromboplastin calibration using plasmas from patients with cirrhosis instead of from vitamin K antagonist patients is feasible and may resolve the variability of the MELD to prioritize patients for transplantation. (HEPATOLOGY 2007.)